Management of Single Rooted Mandibular Second Molar with Single Canal: Two Case Reports - Nidhi Motwani1 , Anuja Ikhar2 , Pradnya Nikhade3 , Rushikesh Bhonde4 , SAkshay Jaiswal4 , Vrushali Z (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The root canals of mandibular molar teeth show a wide variation in its system ranging fromsingle to multiple canals. Thorough understanding of the variations present in internal anatomy of teethis imperative for favorable outcome of the endodontic treatment. The insight of the tooth morphology,variations present related to its root structure, shape and information regarding root canal, with number oforifices and canal configuration, all this should be assessed prior to commence the endodontic treatmentCase Presentation: The present case report describes the variation in second mandibular molar, which isinfrequently mentioned in literature. Variation present may not always be in the form of extra canal, it canbe in the form of fewer or lesser canal than what is usually seen. On inspection of the pulpal floor withendodontic explorer, a single round orifice was seen at the centre of the floor of pulp chamber. Numerousangulated radiographs were obtained to assure the presence of independent single canal. Individual canalpreparation was carried out using ProtaperNiTi instruments (Maillefer, Dentsply) till F5. Using lateralcondensation technique along with sealapex sealer, obturation was carried out.Conclusion: Knowledge of the number of root canals present within the tooth is imperative for successfulroot canal treatment. Some teeth may show extra canals, while other may show fewer than normal numberof canals present. Mandibular second molar may present with single canal and this should be promptlyrecognized. Single canal identification helps to conserve the tooth structure by eliminating the need forremoval of excessive tooth structure in search of extra canal.